RBTT-08. EORTC 1709/CCTG CE.8: A PHASE III TRIAL OF MARIZOMIB IN COMBINATION WITH STANDARD TEMOZOLOMIDE-BASED RADIOCHEMOTHERAPY VERSUS STANDARD TEMOZOLOMIDE-BASED RADIOCHEMOTHERAPY ALONE IN PATIENTS WITH NEWLY DIAGNOSED GLIOBLASTOMA. (5th November 2018) - Roth, Patrick; Reijneveld, Jaap; Gorlia, Thierry; Dhermain, Frederic; Vanlancker, Maureen; Fournier, Beatrice; Nuyens, Sarah; O'Callaghan, Chris; Le Rhun, Emilie; Elias, Ileana; van den Bent, Martin; Mason, Warren; et al.
Abstract: BACKGROUND: The standard of care for patients with newly diagnosed glioblastoma includes maximum safe surgery, involved-field radiotherapy (RT), and concomitant and up to six cycles of maintenance temozolomide (TMZ) chemotherapy (TMZ/RT→TMZ). However, the prognosis remains poor and there is a high unmet need to provide new drugs to patients with glioblastoma. Marizomib is a novel, brain-penetrant irreversible pan-proteasome inhibitor that has been successfully assessed in phase I studies in patients with newly diagnosed as well as recurrent glioblastoma. METHODS: EORTC 1709/CCTG CE.8 is a multicenter, randomized, controlled, open label phase III superiority trial. To be eligible, patients need to have histologically confirmed newly diagnosed glioblastoma. A total of 750 patients will be enrolled and randomized 1:1. Stratification factors include institution, age, Karnofsky performance status and extent of surgery. The primary objective of this study is to compare overall survival in patients receiving marizomib in addition to standard treatment (TMZ/RT→TMZ) with patients receiving standard treatment only. The testing strategy is defined to assess this objective in both the intent-to-treat population and the subgroup of patients with tumors harboring an unmethylated O 6 -methylguanine-DNA methyltransferase (MGMT) promoter. Secondary endpoints include progression-free survival, safety, neurocognitive function and quality of life. An accompanying translational research program has been set up. The study will be opened at 50 EORTC sites in Europe and done as an intergroup collaboration with the Canadian Cancer Trials Group (CCTG) with 25 sites in Canada and additional sites in the US. Patient enrolment is planned to start in June 2018 and an update on the enrolment status will be provided at the SNO conference. ClinicalTrials.gov Identifier: NCT03345095